(untitled) (Indian Journal of Nematology, 2025)
A total of 57 rice genotypes from Assam and adjoining states (3 from Sikkim, 5 from Mizoram, 14 from Arunachal Pradesh, and 35 from Assam) were screened for their resistance against Meloidogyne graminicola under controlled conditions. All 57 rice varieties were found to be susceptible to M. graminicola. A field study on the management of M. graminicola using organic resources revealed that combination of agricultural lime @ 10 kg/ha + FYM @ 1 t/ha + wood ash @ 2 kg/ha in two split doses viz., half as basal application and another half at 45 days after sowing exhibited better result in reducing the M. graminicola population is soil (34.57% reduction over control) as well as in root (43.2% reduction over control). This treatment exhibited the highest per cent increase in yield (44.57% increase over control) as well as other yield-attributing characters. However, the recommended check (application of Pseudomonas fluorescens @ 20 g/m2 at sowing) recorded the best result in reducing the population of M. graminicola, both in soil (34.94%) and roots (50%).